2014
DOI: 10.1007/978-3-319-12568-8_85
|View full text |Cite
|
Sign up to set email alerts
|

Semisupervised Approach to Non Technical Losses Detection

Abstract: Non-technical electrical losses detection is a complex task, with high economic impact. Due to the diversity and large number of consumption records, it is very important to find an efficient automatic method to detect the largest number of frauds with the least amount of experts' hours involved in preprocessing and inspections. This article analyzes the performance of a strategy based on a semisupervised method, that starting from a set of labeled data, extends this labels to unlabeled data, and then allows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…This mechanism uses the concept of transfer learning. Another work done in [37] implements a semi-supervised support vector machine (SVM), named as transductive SVM (TSVM), for ETD by utilizing the labeled and unlabeled information. Likewise, authors in [38] design a deep generative model, termed as semi-supervised autoencoder (SSAE), which makes use of semi-supervised information for ETD.…”
Section: ) Semi-supervised Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism uses the concept of transfer learning. Another work done in [37] implements a semi-supervised support vector machine (SVM), named as transductive SVM (TSVM), for ETD by utilizing the labeled and unlabeled information. Likewise, authors in [38] design a deep generative model, termed as semi-supervised autoencoder (SSAE), which makes use of semi-supervised information for ETD.…”
Section: ) Semi-supervised Solutionsmentioning
confidence: 99%
“…It creates a boundary between classes for class separation. The authors in [37] design a semi-supervised SVM, named as TSVM, to make use of both labeled and unlabeled information. Therefore, we consider it as a baseline.…”
Section: Benchmark Modelsmentioning
confidence: 99%
“…[23] uses Transductive SVM(TSVM) to build a NTL detecting system. Restricted to TSVM could not handle imbalance situation, [23] has not been demonstrated enough for detecting NTL. However, semi-supervised learning still is competitive and hopeful choice for detecting NTL when it meets deep learning.…”
Section: Related Workmentioning
confidence: 99%
“…However, we cannot use SVM to replace these 2 fully connected layers, because it is impossible to co-train SVM and autoencoder together. The separated training will lead to a decline in the learning efficiency, such as [23] could not get satisfactory performance of NTL detection.…”
Section: Framework Of Ssaementioning
confidence: 99%
“…Several pattern recognition approaches have addressed the detection of nontechnical losses, both supervised, unsupervised or recently semi-supervised as shown in [36]. Leon et al review the main research works found in the area between 1990 and 2008 [23].…”
Section: Introductionmentioning
confidence: 99%